2020
DOI: 10.1200/jco.2020.38.15_suppl.2551
|View full text |Cite
|
Sign up to set email alerts
|

Tumor treating fields effects on the blood-brain barrier in vitro and in vivo.

Abstract: 2551 Background: The greatest hurdle, which even potent and effective drugs targeting central nervous system (CNS) tumors and other disorders face, is the blood brain barrier (BBB). The inability to cross the tight regulatory mechanism renders these drugs futile. Of late, administration of tumor treating fields (TTFields) as part of a combined treatment modality for glioblastoma demonstrated increased overall patient survival. Still, the effects of TTFields on the BBB have not yet been investigated. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Using this cell line, it was shown that the administration of frequency-, intensity-, as well as duration- dependent TTFields results in the delocalization of its major tight junction protein claudin-5, as well as the cytoplasmic accessory protein zonula occludens-1 (ZO-1), from the cell membrane boundaries into the cytoplasm ( 82 ). Allowing the cells to recover up to 96h post-TTFields led to the restoration of the original cellular morphology, pointing to the reversibility of the process.…”
Section: Other Biological Effects: Blood–brain Barriermentioning
confidence: 99%
“…Using this cell line, it was shown that the administration of frequency-, intensity-, as well as duration- dependent TTFields results in the delocalization of its major tight junction protein claudin-5, as well as the cytoplasmic accessory protein zonula occludens-1 (ZO-1), from the cell membrane boundaries into the cytoplasm ( 82 ). Allowing the cells to recover up to 96h post-TTFields led to the restoration of the original cellular morphology, pointing to the reversibility of the process.…”
Section: Other Biological Effects: Blood–brain Barriermentioning
confidence: 99%
“…Moreover, this effect can be modulated with the duration of cell membrane permeability dependent upon the length of TTFields exposure. Increased cancer cell permeability may have clinical implications such as increased uptake of chemotherapeutic agents which would be especially important when considering the potential to open up the blood-brain barrier in the treatment of GBM (Salvador et al 2020).…”
Section: Ttfields Induced Mechanisms Of Actionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 The anti‐tumor mechanisms of action of TTFields are also associated with influencing tumor cell migration, increasing the permeability of tumor cell membranes and the blood‐brain barrier, inducing autophagy in tumor cells, increasing DNA damage, and inducing antitumor immunity. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 TTFields have been approved by the FDA for recurrent and newly diagnosed GBM based on the results of clinical studies in EF‐11 and EF‐14. 14 , 32 In addition, TTFields have been approved for the treatment of mesothelioma and are currently being studied in many other tumor types including non‐small cell lung cancer, pancreatic cancer, ovarian cancer and so on.…”
Section: Introductionmentioning
confidence: 99%
“…TTFields interfere with mitosis in tumor cells by disrupting microtubulin polymerization, septal localization, and cytokinesis, preventing mitotic spindle assembly, and adjusting cellular membrane potential to increase the influx of intracellular Ca 2+ to promote microtubulin depolymerization, which causes cell cycle arrest, and ultimately leads to tumor cell death/apoptosis 15–22 . The anti‐tumor mechanisms of action of TTFields are also associated with influencing tumor cell migration, increasing the permeability of tumor cell membranes and the blood‐brain barrier, inducing autophagy in tumor cells, increasing DNA damage, and inducing antitumor immunity 23–31 . TTFields have been approved by the FDA for recurrent and newly diagnosed GBM based on the results of clinical studies in EF‐11 and EF‐14 14,32 .…”
Section: Introductionmentioning
confidence: 99%